Contemporary financial intermediation. - Greenbaum, Stuart I.; Thakor, Anjan V.; Boot, Arnoud W. A. (Willem Alexander), 1960- (Academic Press, 2019)
Instead of primarily naming and describing markets, regulations, and institutions as is common, Contemporary Financial Intermediation explores the subtlety, plasticity and fragility of financial institutions and credit markets. In this new edition every chapter has been updated and pedagogical supplements have been enhanced. For the financial sector, the best preprofessional training explains the reasons why markets, institutions, and regulators evolve they do, why we suffer recurring financial crises occur and how we typically react to them.